Human rights and African airwaves : mediating equality on the Chichewa radio - Englund, Harri (Indiana University Press, 2011)
Human Rights and African Airwaves focuses on Nkhani Zam'maboma, a popular Chichewa news bulletin broadcast on Malawi's public radio. The program often takes authorities to task and questions much of the human rights rhetoric that comes from international organizations. Highlighting obligation and mutual dependence, the program expresses, in popular idioms and local narrative forms, grievances and injustices that are closest to Malawi's impoverished public. Harri Englund reveals broadcasters' everyday stru.